Omohyoid muscle syndrome - Maengkom, Fika Amanda; Adiputra, Putu Anda Tusta (International Journal of Research in Medical Sciences, 2020)
Omohyoid muscle syndrome is a rare cause of a bulging lateral neck mass that occurs on swallowing that often a worrisome observation because of the concern of malignancy and cosmetic deformity. The first case has been documented on 1969. A 12 years old male came to Surgical Oncology Outpatient Clinic with chief complaint a protruding right lateral neck mass during swallowing. He noticed this complaint since three months prior. He had no previous history of medical illness. He had history of multiple chokehold trauma when playing with his friend 6 months ago. He had no symptoms besides the mass occurring on his right neck. The patient went through the cervical radiograph and neck ultrasonography examination. There were inconclusive results. The patient was informed that the implication of these findings was strictly cosmetic and did not pose any risk of long-term consequence. Corrective cosmetic surgery was recommended as an option if he was concerned about the cosmetic appearance and conservative management was recommended to observe any pain or dysphagia he might experience in the near future. He denied surgery and did not seek further care for his condition. Omohyoid muscle syndrome is a rare condition that might occur after trauma such as chokehold to the neck. Imaging on this syndrome quite challenging especially when there were no other symptoms experienced. If it is proven to be strictly cosmetic, most patients will choose to have a conservative therapy.